2022
DOI: 10.1080/2162402x.2022.2138152
|View full text |Cite
|
Sign up to set email alerts
|

Human allogenic γδ T cells kill patient-derived glioblastoma cells expressing high levels of DNAM-1 ligands

Abstract: Adoptive transfer of γδ T cells is a novel immunotherapeutic approach to glioblastoma. Few recent studies have shown the efficacy of γδ T cells against glioblastoma, but no previous studies have identified the ligand–receptor interactions between γδ T cells and glioblastoma cells. Here, we identify those ligand–receptor interactions and provide a basis for using γδ T cells to treat glioblastoma. Vγ9Vδ2 T cells were generated from peripheral blood mononuclear cells of healthy donors using artificial antigen pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Vγ9Vδ2 T cell immunotherapy offers a promising approach. In this study, we demonstrated that Vγ9Vδ2 T cells derived from healthy human PBMCs inhibited GBM cell proliferation in vitro and suppressed GBM tumor growth in vivo without apparent toxicity to mice, consistent with recent reports [ 35 37 ]. However, the response to Vγ9Vδ2 T cell therapy varied greatly among PTCs, leading us to classify them into SAT and WAT groups.…”
Section: Discussionsupporting
confidence: 92%
“…Vγ9Vδ2 T cell immunotherapy offers a promising approach. In this study, we demonstrated that Vγ9Vδ2 T cells derived from healthy human PBMCs inhibited GBM cell proliferation in vitro and suppressed GBM tumor growth in vivo without apparent toxicity to mice, consistent with recent reports [ 35 37 ]. However, the response to Vγ9Vδ2 T cell therapy varied greatly among PTCs, leading us to classify them into SAT and WAT groups.…”
Section: Discussionsupporting
confidence: 92%
“…We first focused on DNAM-1 and its ligands, PVR and nectin-2, emerging players in tumor immunology, 11 previously shown to be important for Vδ2 + γδ T-cell responses to liver or brain cancers. 12 , 13 , 14 We used blocking antibodies in 3-hour killing assays against HEL or MOLM13 AML cells, and found a 20% to 30% decrease in DOT-cell cytotoxicity upon DNAM-1 neutralization ( Figure 1 D-E). However, because ligand blockade failed to reproduce this effect, we used a more stringent methodology, CRISPR–CRISPR-associated protein 9 gene editing, to knock out each or both ligands ( Figure 1 F).…”
Section: Resultsmentioning
confidence: 97%
“…The mode of action of gd T cells in an anti-tumor response comprises direct cytolytic activity via NKG2D, FcyRIII, Fas/Fasligand, DNAM-1 receptor-ligand interaction and the TNF related apoptosis inducing ligand (TRAIL) pathway resulting in production of perforins, granzymes, IFN-g and TNF-a (4,5,(18)(19)(20)(21)(22)(23). In concurrence, gd T cells can also activate other immune cells (24,25), for instance activate NK cells via co-stimulation, promote dendritic cell (DC) maturation and support initiation of a humoral immune response (26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%